The power of naming students-as-partners practices - Casey, Alison (International Journal for Students as Partners, 2024)
Involving students in the design of their educational experience is increasingly being understood by higher education institutions to enhance learning, to build a better culture, and to foster inclusivity amongst a host of other benefits. Accordingly, institutions are trialling a wide range of Students as Partners practices. There is currently huge variation in the nature and scale of these practices. This paper proposes a taxonomy that will allow Students as Partners practices to be consistently described, and therefore compared and mapped. This is a vital next step in the development and widespread adoption of this transformational set of practices.